Masked and white coat hypertension, the double trouble of large arteries: A systematic review and meta‐analysis - Antza, Christina (J Clin Hypertens (Greenwich), 2020)
Arterial damage of large arteries, addressed as c‐f PWV, is recognized as independent predictor for future cardiovascular disease. The aim of this study was to systematically investigate the association of the four hypertension phenotypes with carotid‐femoral pulse wave velocity (c‐f PWV), in untreated patients. PubMed and Cochrane Library were searched to identify studies comparing c‐f PWV levels between normotensives, sustained hypertensives, white‐coat hypertensives (WCH), and masked hypertensives (MH). Meta‐analysis was performed to compare the difference c‐f PWV levels between these groups. Newcastle‐Ottawa quality assessment scale for cross‐sectional studies was used to assess study quality. MH and WCH patients had significantly increased c‐f PWV values compared to the normotensive groups (d = 0.96 m/s, 95% CI: 0.49‐1.42; I2 = 85%, P < .01 for MH and d = 0.85 m/s, 95% CI: 0.48‐1.22; I2 = 89%, for WCH). Moreover, the sustained hypertensive population was found to have significantly increased values of c‐f PWV compared to MH (d = −0.70 m/s, 95% CI: −0.87 to −0.54; I2 = 12%, P = .33) but not compared to WCH population (d = −0.75 m/s, 95% CI: −1.52‐0.02; I (2) = 96%,). Finally, there was no significant difference between MH and WCH population (d = 0.06 m/s, 95% CI: −1.04 to 1.15; I (2) = 96%,). MH and WCH population may have increased values of c‐f PWV compared to the normotensive group. These results demonstrate that these phenotypes are not clinically innocent, in the untreated population.